Necessidades e uso de informação: um estudo com médicos de Unidades de Saúde da Família. - Albuquerque, Ednaldo Maciel (2010)
Information is considered an indispensable phenomenon to man‟s life and survival, and the association between this phenomenon and the human being is very relevant and significant because it is an object of research and study in many areas of knowledge. For a better comprehension about this phenomenon and its connection with the human being, a research was developed to analyze the necessities and uses of information of the doctors in the Family Health Units of Distrito Sanitário III, in João Pessoa PB. The mentioned research used the assumptions of the information user studies, under the egis of the Modern Paradigm and the Sense-Making methodological approach. The sample is formed by 28 doctors linked to the Family Health Units. Moreover, the data collection tools were questionnaire and interview. The results revealed that the doctors can satisfy their necessities of information by using the Internet and books. However, they face obstacles in relation to the use of information like the lack of time, which is the most frequent. Furthermore, they cheer up to use the information in the Health Units and, in an incipient way, they give meaning and sense to the obtained information. Therefore, it can be concluded that the trinomial situation-gap-use, which are professed by the Sense-Making, is evident in the quotidian of the Family Health Units doctors, relative to the necessity, inquiry and use of information